2017
DOI: 10.1080/15592324.2017.1382795
|View full text |Cite
|
Sign up to set email alerts
|

Farnesylation-mediated subcellular localization is required for CYP85A2 function

Abstract: Protein farnesylation refers to the addition of a 15-carbon farnesyl isoprenoid to the cysteine residue of the CaaX motif at the carboxy terminus of target proteins. In spite of its known roles in plant development and abiotic stress tolerance, how these processes are precisely regulated by farnesylation had remained elusive. We recently showed that CYP85A2, the cytochrome P450, which converts castasterone to brassinolide in the last step of brassinosteroid synthesis must be farnesylated in order to function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Farnesylation, a post-translational modification, of Arabidopsis CYP85A2/BR6ox2 was found to be essential for its subcellular localization and function. Loss of CYP85A2/BR6ox2 farnesylation results in reduced BL accumulation, similar to the mutation of CYP85A2/BR6ox2 ( Northey et al, 2016 ; Jamshed et al, 2017 ). In rice, RAVL1 and RAV6, two homologous B3 transcription factors, mediate activation of both OsBRI1 and the BR biosynthetic genes that have antagonistic actions on BR levels to ensure the basal activity of the BR signaling and biosynthetic pathways ( Il Je et al, 2010 ; Zhang et al, 2015 ).…”
Section: Br Biosynthesis Pathwaysmentioning
confidence: 75%
“…Farnesylation, a post-translational modification, of Arabidopsis CYP85A2/BR6ox2 was found to be essential for its subcellular localization and function. Loss of CYP85A2/BR6ox2 farnesylation results in reduced BL accumulation, similar to the mutation of CYP85A2/BR6ox2 ( Northey et al, 2016 ; Jamshed et al, 2017 ). In rice, RAVL1 and RAV6, two homologous B3 transcription factors, mediate activation of both OsBRI1 and the BR biosynthetic genes that have antagonistic actions on BR levels to ensure the basal activity of the BR signaling and biosynthetic pathways ( Il Je et al, 2010 ; Zhang et al, 2015 ).…”
Section: Br Biosynthesis Pathwaysmentioning
confidence: 75%
“…Earlier reports showed that farnesylation of BR6ox2 is essential for its normal subcellular localization and function ( Northey et al, 2016 ; Jamshed et al, 2017 ). In addition, the levels of a number of BRs, including 6‐deoxocastasterone (6‐deoxo CS), castasterone (CS), and BL are altered in br6ox2‐2 and era1‐2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of farnesylation in regulating plant growth and development are very limited ( Running, 2014 ). It was reported that CYP85A2 (also known as BR6ox2), a cytochrome P450 enzyme that catalyzes the last step in the brassinolide (BL) biosynthesis pathway by converting castasterone (CS) to BL, is farnesylated in Arabidopsis ( Kim et al, 2005 ; Northey et al, 2016 ; Jamshed et al, 2017 ). The farnesylation of BR6ox2 is required for its endoplasmic reticulum (ER) localization and function.…”
Section: Introductionmentioning
confidence: 99%